Analisis Harga Saham Perusahaan Sub-Sektor Games yang Terdaftar di NASDAQ (2012-2022) - Ira Setiawati; Rita Meiriyanti; Yoga Indra Khatama (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
This paper examines the stock prices of gaming sub-sector companies listed on NASDAQ from 2012 to 2022, focusing on how financial ratios affect stock prices in this significant and rapidly growing sector of the global Entertainment & Media industry. The primary issue addressed is the impact of financial ratios on stock prices, with the research question centered on how the Current Ratio (CR), Net Profit Margin (NPM), and Return on Equity (ROE) affect stock prices. The novelty of this study lies in its focus on the under-researched gaming sub-sector on NASDAQ. Employing a purposive sampling approach, the study selects companies based on criteria such as being listed on NASDAQ, having complete data for the study variables, and conducting an IPO before 2012, and uses panel data regression analysis to test the effects of CR, NPM, and ROE on stock prices. The findings reveal that the Current Ratio and Net Profit Margin do not significantly affect stock prices, whereas Return on Equity has a significant effect, underscoring ROE's importance in influencing investor decisions in the gaming industry. The study concludes that only ROE significantly affects stock prices in the gaming sub-sector on NASDAQ, suggesting that gaming companies need to focus on enhancing their ROE to attract investors, highlighting the necessity for a strategic emphasis on return on equity to influence investment decisions effectively.